Invited Editorial: The Gifts of a Talk with TED - James C. Field (University of Calgary, 2021)
In this invited editorial, Dr. Jim Field reflects on the recent meeting of the 12th annual Canadian Hermeneutic Institute, which hosted Professor Ted George as our visiting scholar. Three days of lecture and scholarly conversation left all of us in thoughtful and interpretive spaces.